G246(P) Not all those soft tissue bruises are non accidental injuries. (7th April 2014) - Lall, RK; Jayatunga, R
Abstract : Aim: To present an interesting case of soft tissue bruising suspected of Non accidental injury which turned out to be a rare clotting abnormality highlighting the importance of extended clotting studies in suspected Non accidental injury. Methods: A 5 year old female was admitted with viral induced wheeze. On examination widespread soft tissue bruising was noted on arms, thighs, calves and back. She was born at term. No bleeding problems perinatally or prolonged bleeding from umblical cord noted. She had uneventful immunizations (no haematomas). There was a past history of easy bruising for 3 years. Parents were first cousins. There was no family history of easy bruising. She was 1 of 3 siblings (2 other sisters were well). The 6 year old sibling had disclosed domestic abuse to the school teacher early that year. When investigated, parents denied the allegation and the child retracted the information. Case was closed by Social services. Clinical photographs done and blood results including APTT, PT, FBC, Platelets, Blood film, LFT & Von Willebrand screen were normal. Results: Feedback from safeguarding nurse and school raised no further concerns. Follow up revealed significant fresh bruising on soft tissue areas. The child was referred to our tertiary haematology centre for further specialist tests which suggested abnormal platelet aggregation as the cause of the bruising. Conclusion: This case emphasises the key issue of how far the investigations should be pursued to exclude a pathological cause. There is a need to apply extended clotting studies to exclude clotting abnormalities in all cases of bruising where there is a suspicion of non-accidental injury.